Flow Hydrodynamic in Open Channels Interaction with Natural or Man-Made Structures - Ben Meftah, Mouldi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Streams and rivers are subject to considerable hydrodynamic loads. Flow interactions with natural or man-made structures in open channels lead to the development of complex dynamic processes, requiring further studies to comprehend fully. This Special Issue has been conceived to facilitate improvement or propose new approaches, summarize the most important findings of previous studies, and encourage the development of further knowledge in the field of open-channel flows. Various topics are addressed in this SI, including flow interaction with hydraulic structures, flow dynamics in estuaries, flow-vegetation interactions, bed sediment effects on flow structures, and the effect of channel curvature on flow behaviors and sediment transport. The studies published in this Special Issue certainly help readers understand the turbulent flow involved in open channels and apply that understanding to the design and practice of hydraulic engineering and river management.